The Church’s Ethical Responsibilities towards Net-Zero Carbon Emissions Objectives - TANHIDY, Jamin; NDAPAMURI, Yohanis; YEREMIA; GUILD, Rebecca Joy (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
The overuse of fossil fuels and growing industrialisation throughout the world have caused greenhouse gases to be released, raising the global temperature and posing global environmental problems. Therefore, achieving net-zero carbon emissions is imperative. Net-zero carbon emissions can be attained by balancing the entire amount of carbon dioxide or greenhouse gas emissions over a period of time and making environmentally sustainable initiatives. For environmental sustainability to be successful, it must have a means of translating into environmentally friendly attitudes and actions of humans towards the environment. The Christian faith teaches that the earth is the Lord’s and that humans have moral responsibility as "stewards." Thus, Christians and the Church corporately have a basic role in achieving net-zero carbon emissions. This paper presents a systematic discussion using the Indonesian Church as a case study to look at the moral responsibilities of the corporate church in attaining net-zero carbon emissions. This work employs the research method of "content analysis" to examine both the primary and secondary existing literature on the research topic. This essay first identifies the theological role of the church in addressing environmental issues, which implies understanding the stewardship mandate that God has placed on humans to care for the earth. This paper also discussed the educational role of the corporate church in educating its adherents. Lastly, from the practical aspect, this paper discussed how and why the Indonesian church should support the government’s programmes (such as the Green Village program) to help overcome the environmental crisis.